2014
DOI: 10.3390/su6106998
|View full text |Cite
|
Sign up to set email alerts
|

UASB followed by Sub-Surface Horizontal Flow Phytodepuration for the Treatment of the Sewage Generated by a Small Rural Community

Abstract: Abstract:The paper presents the results of an experimental process designed for the treatment of the sewage generated by a rural community located in the north-east of Brazil. The process consists of a preliminary mechanical treatment adopting coarse screens and grit traps, followed by a biological treatment in a UASB reactor and a sub-surface horizontal flow phytodepuration step. The use of a UASB reactor equipped with a top cover, as well as of the phytodepuration process employing a porous medium, showed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…Total and faecal coliform removal efficiencies achieved in the constructed wetland system was comparable to the efficiencies reported in the study of Ottov a et al (1997) ranging usually between 98.1 and 99.9%. Other studies also showed coliform removal efficiencies of 98.8% on average in CWs (Masi et al 2008;Raboni et al 2014).…”
Section: Pathogens Analyses Of Wetland Influent and Effluentmentioning
confidence: 82%
“…Total and faecal coliform removal efficiencies achieved in the constructed wetland system was comparable to the efficiencies reported in the study of Ottov a et al (1997) ranging usually between 98.1 and 99.9%. Other studies also showed coliform removal efficiencies of 98.8% on average in CWs (Masi et al 2008;Raboni et al 2014).…”
Section: Pathogens Analyses Of Wetland Influent and Effluentmentioning
confidence: 82%
“…The UASB-CW integration indicates the following abatement efficiencies with regard to BOD5 (92.9%), COD (79.2%), SS (94%), and fecal coliforms (98.8%) were achieved compared with single UASB treatment efficiencies shown in Fig. 6 (Raboni et al 2014). Other post-treatment techniques (Fig.…”
Section: Anaerobic (Ubf)-aerobic (Mbr) Reactormentioning
confidence: 88%
“…The anaerobic bacteria in the granular sludge removes organics and is one of the most important components of the bio-reactor. At present, granule-based reactors include upflow anaerobic sludge blanket (UASB), internal circulation (IC), and expanded granular sludge blanket (EGSB) [7,8]. In developing countries, the decentralized approach has been adopted where small-scale biogas 2 of 15 plants are utilized to transform waste into gas through anaerobic fermentation of organic materials [9].…”
Section: Introductionmentioning
confidence: 99%